The Case of Qualitative Genetics in Fish - Tariq, Safaa (International Journal Papier Advance and Scientific Review, 2020)
Character inheritance or heredity is the inheritance of traits from parents to their children (offspring). The event or process by which a cell of an organism tends to become or possess the characteristics of its parents. The discovery of recombinant DNA opened up developments in genetic engineering. Genetic engineering technology provides a lot of hope for us in various areas of need including gene therapy efforts. Inheritance is the traits or traits of living things that are passed down from generation to generation or passed down from parent to offspring. The traits of a living being are inherited through male sex cells and female sex cells. Normal pigmented goldfish are mated with yellow-striped goldfish on the dorsal spine to produce 100% fish with yellow lines on the dorsal spine.